Reading ability and academic acculturation: The case of South African students entering higher education - van Dyk, Tobie; Van de Poel, Kris; van der Slik, Frans (Stellenbosch Papers in Linguistics Plus, 2014)
First-year students experience a range of challenges when transferring from secondary to higher education (HE) (cf. Darlaston-Jones et al. 2003, Leki 2006, Brinkworth et al. 2009). This is no different in South Africa, where deviating levels of preparedness for the demands of HE is a recurring theme (Slonimsky and Shalem 2005, Van Schalkwyk 2008, Scott 2009, Yeld 2009, Van Dyk 2010, Van Dyk and Coetzee-Van Rooy 2012). Weideman (2003:56) rightfully points out that the inability to understand and utilise appropriate academic discourse has a detrimental effect on academic success. Young students need to acculturate to the academic environment while adopting the academic community’s currency (Van de Poel and Gasiorek 2012a:294). With this article, we wish to contribute to the discussion by reporting on the academic language ability of one group of first-year students at a South African university, with specific reference to these students’ reading ability, on the basis of the following data: (i) individual differences in terms of learner characteristics (race, first language, gender, Grade 12 results, academic performance); (ii) self-reported reading preparedness, and (iii) reading profiles resulting from a valid and reliable academic literacy test, the Test of Academic Literacy Levels (TALL) and its Afrikaans counterpart, the Toets van Akademiese Geletterdheidsvlakke (TAG). The findings suggest that academic reading ability, as reflected in the test results, is indeed one of the salient contributors to academic success (as confirmed in the literature), regardless of social and individual differences, and that it needs to be supported in order for students to perceive their reading ability in accordance with their reading performance and be able to progress in their academic acculturation. A follow-up study will report on students’ awareness-raising about their own academic reading through the use of the validated scale for Perceived Academic Reading Preparedness (PARP) as a pedagogical tool.